The Role of Economic Policies to Adopt Renewable Energy and Digital Technology on Business Decisions and HR Management in the Indonesian Mining Sector - Nalom Siagian (International Journal of Energy Economics and Policy, 2024)
The problem formulation that arises from this research is how the direct and indirect effects of renewable energy adoption variables and digital technology adoption affect the business decisions of mining companies in Indonesia with HR management variables as intervening variables. The subjects of this research are leaders in mining companies in Indonesia totaling 390 business units, where the variables in this study are independent variables, namely the adoption of renewable energy and the adoption of digital technology, while the dependent variable is the business decisions of mining companies in Indonesia, and the intervening variable is the HR management variable, where data analysis uses path analysis using Amos 22 software. The research method carried out is to use a quantitative descriptive approach by using data analysis with the path analysis method, where the results of data processing with the path analysis method are carried out with the Amos 22 application. From the results of this study, the conclusions that exist, namely partially the variable adoption of renewable energy and the variable adoption of digital technology, have a direct effect on the business decisions of mining companies in Indonesia. Renewable energy adoption variables partially also have a direct effect on HR management of mining companies in Indonesia, and HR management variables of mining companies in Indonesia have a direct effect on business decisions of mining companies in Indonesia. Simultaneously, the renewable energy adoption variable and the digital technology adoption variable indirectly affect the business decisions of mining companies in Indonesia through HR management as an intervening variable. With the process of adopting renewable energy and adopting digital technology, it will create changes to the business decision process carried out by the mining industry in Indonesia regarding HR management to become human resources capable of managing these changes. The government must carry out economic policies that support these changes, such as providing industrial incentives that are willing to change and adopt renewable energy and digital technology in order to compete and create products that are able to reduce the risk of climate change.